Intersex People in Aotearoa New Zealand: The Challenges for Law and Social Policy: Part I: Critiquing Gender Normalising Surgery - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2015)
In this first of two articles dealing with the current issues facing intersex people in Aotearoa New Zealand, the author focuses on what is seen by community activists as their most pressing concern: ongoing genital normalising surgery on intersex infants. The resolution of this issue sits at the interface of criminal law, medical law and family law, and requires nuanced and careful engagement with competing norms of social policy. The article defines "intersex", as compared to "trans", and considers how infant surgery is currently (under)regulated in spite of local and international calls for reform. The author argues that it is time serious consideration is given to legislative regulation of surgery on intersex infants, following overseas initiatives, including the recent enactment in the Republic of Malta.